That's what friends are for ; New sons or nuissance ; Filing the gap [videorecording] - Lazaro, Cheche (THe Probe Team, 1989)
Tackles Fil-Am relationship and mental colonialism ; annual selection of SONS, UP Diliman College of Law; and NBI raid on Ana Araneta Ocampo who was charged as baby trafficker.